2017
DOI: 10.1177/0340035216688703
|View full text |Cite
|
Sign up to set email alerts
|

Managing research data at an academic library in a developing country

Abstract: Managing research data has become an issue for many universities. In the Caribbean, the St Augustine Campus Libraries at the University of the West Indies are keenly aware of the need to support researchers in this regard. The objectives of this study were to identify current practices in managing research data on the campus and to determine a possible role for the Campus Libraries. A pilot study of 100 researchers on the campus was conducted. Analysis of the 65 valid responses revealed that while researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Buys and Shaw (2015) found that social and humanities researchers prefer long-term (even unlimited) data storage. Diversity was also confirmed in other studies, which investigated researchers from different areas (Schumacher and VandeCreek, 2015; Buys and Shaw, 2015; Weller and Monroe-Gulick, 2014; Renwick et al , 2017). In the area of medicine, Piwowar (2011) identified 15 factors influencing researchers’ preparedness to share their data, divided into five categories: authorship, funding, institution, publication and domain environments.…”
Section: Introduction and Literature Surveysupporting
confidence: 77%
“…Buys and Shaw (2015) found that social and humanities researchers prefer long-term (even unlimited) data storage. Diversity was also confirmed in other studies, which investigated researchers from different areas (Schumacher and VandeCreek, 2015; Buys and Shaw, 2015; Weller and Monroe-Gulick, 2014; Renwick et al , 2017). In the area of medicine, Piwowar (2011) identified 15 factors influencing researchers’ preparedness to share their data, divided into five categories: authorship, funding, institution, publication and domain environments.…”
Section: Introduction and Literature Surveysupporting
confidence: 77%
“…The interview subjects demonstrated uncertainty about data sharing, problems with data storage, and significant interest in library support with these aspects of data management. Similarly, Renwick et al (2017) conducted a pilot study of 100 researchers across disciplines at the University of the West Indies in the Caribbean and found from the 65 valid responses a lack of knowledge in data management best practices. For example, 66% of respondents used flash-drives as a data storage method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Libraries have to play an active role in sensitising the researchers towards the importance of properly documenting, organising and preserving datasets for future. Generally, the researchers are not aware of the importance of preserving research datasets for future 24 . They lack the ability to express their data management plans and how they will preserve and share them in future 31 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…They lack the ability to express their data management plans and how they will preserve and share them in future 31 . The librarians are expected to support researchers in their research data plans and practices and provide the technical infrastructure and support for actual data storage 24 . These services should not be one size fits all.…”
Section: Literature Reviewmentioning
confidence: 99%